Cross sectional analysis of muscular strength and flexibility during the menstrual cycle in women engaged in strength training - Maria Vitória do Nascimento Pereira; Pedro Pinheiro Paes; Marlene Salvina Fernandes Costa; Igor Lima Tavares Freitas; Rubem Cordeiro Feitosa; José Manuel Delfa de la Morena; Walmir Romário Santos; Wlaldemir Roberto Santos (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Hormonal variations during the menstrual cycle (MC) impact muscular strength and flexibility in women practicing strength training, potentially leading to performance reductions and increased injury susceptibility. Understanding these variations across MC phases is crucial for precise training program guidance. This cross-sectional, exploratory study assessed muscular strength and flexibility levels during the MC in 20 women (aged 20-35) engaged in strength training for at least 6 months. The Sit and Reach Test (SRT) measured flexibility, and the 1-Maximum Repetition Test (1RM) leg extension evaluated muscular strength during menstrual, post-menstrual, and pre-menstrual phases. While the post-menstrual period showed the highest strength values (50.65 ± 17.70 kg), no significant differences were observed compared to other phases. However, flexibility was significantly higher in the post-menstrual period (29.43 ± 8.69 cm) compared to menstrual (p=0.002) and pre-menstrual phases (p=0.001). Statistically, no significant differences were found in strength performance. Nevertheless, flexibility appeared influenced by MC phases, with superior outcomes in the post-menstrual period. This research enhances our understanding of how MC phases may impact strength and flexibility in women engaged in strength training, providing valuable insights for tailoring training programs to individual needs.